2020
DOI: 10.18502/sjms.v15i4.8161
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Theory to Inform Practice – Theorizing the Current Trends of Clinical Teaching: A Narrative Review

Abstract: Clinical teaching lies at the heart of physicians’ training; however, it is often opportunistic, haphazard, and lacks a theoretical foundation. Medical education is a profession that requires robust scientific methods and an evidence-based approach driven by accountability and patient safety concerns in the healthcare provision nowadays. Learning theories are increasingly applied in the realm of medicine with implications to the quality of teaching and learning in the clinical environment and the professional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(278 reference statements)
0
1
0
Order By: Relevance
“…Students are well-aware that learning occurs through practise, thus they positively respond to constructive feedback during evaluations (Selvaraj et al, 2021). Omer (2020) suggested that feedback on evaluation should be constructive for effective teaching and learning process. Instead Wisniewski et al (2020) analysed 435 studies the effect of effective feedback on students' academic progress.…”
Section: Constructive Feedback and Students' Academic Achievementmentioning
confidence: 99%
“…Students are well-aware that learning occurs through practise, thus they positively respond to constructive feedback during evaluations (Selvaraj et al, 2021). Omer (2020) suggested that feedback on evaluation should be constructive for effective teaching and learning process. Instead Wisniewski et al (2020) analysed 435 studies the effect of effective feedback on students' academic progress.…”
Section: Constructive Feedback and Students' Academic Achievementmentioning
confidence: 99%